2003
DOI: 10.1081/jas-120017980
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids for Asthma: Common Clinical Quandaries

Abstract: This narrative review provides evidence-based explanations to some of the common clinical concerns regarding inhaled corticosteroids. Inhaled corticosteroids are the treatment of choice for a newly diagnosed asthmatic patient. Better results are obtained when treatment is initiated as soon as the diagnosis is made. Asthma control can be achieved and maintained in most patients with a low or moderate dose of inhaled corticosteroid administered in two daily doses. Longer duration of treatment provides more susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…50 The efficacy of ICS in asthma control has been clearly demonstrated in both children and adults. 51 However, paradoxically, some investigators conclude that ICS may not prevent asthma exacerbations accompanying RVIs 52-54which are associated with the majority of exacerbations in adults and over 80% in children 13 14 -and that ICS should not be prescribed for mild intermittent viral infection associated asthma, particularly in children. 55 56 The results of three clinical investigations that have examined the effects of ICS in RVI associated asthma exacerbations bear close scrutiny.…”
Section: Asthma Control and Asthma Exacerbationsmentioning
confidence: 99%
“…50 The efficacy of ICS in asthma control has been clearly demonstrated in both children and adults. 51 However, paradoxically, some investigators conclude that ICS may not prevent asthma exacerbations accompanying RVIs 52-54which are associated with the majority of exacerbations in adults and over 80% in children 13 14 -and that ICS should not be prescribed for mild intermittent viral infection associated asthma, particularly in children. 55 56 The results of three clinical investigations that have examined the effects of ICS in RVI associated asthma exacerbations bear close scrutiny.…”
Section: Asthma Control and Asthma Exacerbationsmentioning
confidence: 99%
“…Unfortunately, the long-term effects of multiple administrations of corticosteroids (especially in recurrent cases) are rarely considered. Long-term corticosteroid therapy has been linked to decreased bone mineral density (9). In addition, there are many conservative treatments such as rest, fluids, warm salt water gargling, and anesthetic lozenges, which might provide beneficial effects without accompanying risk of adverse events (10).…”
Section: Discussionmentioning
confidence: 99%
“…Even in children with wheeze, a recent randomized controlled trial in 200 children (1-5 years) found that oral steroids conferred no benefit [119], but was associated with a non-significant increase in hospitalizations (p=0.058). Given that low dose inhaled corticosteroids have been shown to be effective in the management of the majority of childhood asthma [120,121,122] and the reported significant adverse events on high doses [123,124], a dose at 400ug/day equivalent of budesonide or beclomethasone is suggested if a trial of asthma therapy is warranted. As the earlier studies in adults and children that utilized medications for asthma for the era (i.e.…”
Section: Asthma Therapymentioning
confidence: 99%